Analisis Cemaran Logam Berat Timbaldan Kadmium Pada Produk Kosmetika BB Cream - Ganea Qorry Aina; Dini Indriaty Yusran; Tiara Dini Harlita; Puput Uswatun Hasanah; Muhammad Ivan Saputra (CV. Wadah Publikasi Cendekia, 2023)
Blemish Balm Cream (BB Cream), is a cosmetic product that is often used by women. In the composition of BB Cream, there are basic ingredients, one of which is a coloring agent that has many contaminants such as lead and cadmium. Dyes such as CI. 77492 or called iron oxide already contains lead and cadmium with levels < 10 and < 5 ppm. Long-term exposure to lead and cadmium can cause kidney damage and impaired nerve function. The purpose of this study was to determine that the levels of lead and cadmium in BB Cream circulating in the Samarinda area had met the safe limit. This research is a descriptive study using Atomic Absorption Spectrophotometry method. The variables in this study are the independent variables, namely the levels of lead and cadmium in BB Cream circulating in the Samarinda area. The results of measuring the levels of lead and cadmium in 10 samples of BB Cream showed that the levels of lead and cadmium in the tested BB Cream did not exceed the contamination limit. Based on this research, it can be concluded that there are lead and cadmium content from 10 samples, and of these 10 samples all 100% contain lead and cadmium and meet the requirementsfor the standard lead contamination 10 ppm and standard cadmium 5 ppm.